The Impact of Advertising on Consumer Brand Preference: A Focus on Soft-Drink Brands in Nepal - Thakur, Binay Kumar; Singh, Balgopal (The Gaze: Journal of Tourism and Hospitality, 2024)
In the soft drink sector in Nepal, this research investigates the influence that advertising has on the preferences of consumers regarding brand names. In light of the growing significance of advertising as a method for building brand equity, the purpose of this study is to investigate how various advertising mediums, including television, social media, and print, influence consumers' preferences for soft drink companies. Additionally, the research explores the influence that advertising frequency and digital media have in molding brand memory, especially among younger consumers. A quantitative technique was used, and data was gathered through a structured questionnaire sent to two hundred respondents in Nepal who came from various age groups and socio-economic backgrounds throughout the country. The data was analyzed using regression analysis, chi-square testing, and correlation analysis to determine the links between advertisement exposure, brand memory, and brand choice. According to the data, social media has emerged as the most effective medium, particularly among younger customers, which indicates that television advertising and social media are the most potent factors in generating consumer preference for brands. The influence of print media is substantially decreased compared to that of internet and television advertising, even though print media is still essential. As a further point of interest, the findings indicate that a greater advertising frequency is positively connected with enhanced brand memory. Frequent exposure to commercials plays a significant role in maintaining consumer awareness and brand loyalty. The research has important implications for businesses that sell soft drinks, stressing the need to emphasize digital and social media platforms strategically. These platforms are crucial for attracting younger customers who are very knowledgeable about technology. It is possible that print advertising has to be reevaluated, whilst television continues to be an effective medium for reaching a wider audience. The study recognizes its limitations, such as the fact that it was only conducted in Nepal and that the sample size was inadequate. It also advises that future research should investigate cross-national comparisons and the impact that digital advertising has on brand loyalty over the long term.